Effect of solid-to-solvent ratio on phenolic content and antioxidant capacities of “ Dukung Anak” (Phyllanthus niruri) - Wong, B. Y.; Tan, Chin Ping; Ho, C. W. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
The objective of this study was to evaluate the effects of solid-to-solvent ratio (1:5. 1:10, 1:15 and 1:20) on the extraction of phenolic compounds (TPC and TFC) and antioxidant capacity (ABTS and DPPH radical scavenging capacity) of P. niruri . Solid-to-solvent ratio showed a significant effect for both phenolic compounds (TPC and TFC) and antioxidant capacity (ABTS and DPPH radical scavenging capacity) with 1:20 was the condition for extracting the highest of phenolic compounds (TPC and TFC) with a value of 5788.7 mg GAE/100 g DW and 1906.5 mg CE/100 g DW, respectively and exhibited high antioxidant capacities (ABTS and DPPH radical scavenging capacities) with a value of 0.820 mM and 1.598 mM, respectively among the four levels studied. TPC was positively and significantly correlated with ABTS and DPPH (r=0.999 and r=0.999) under the effects of solid-to-solvent ratio as compared to TFC, positively and strongly correlated (r=0.865 and r=0.868) with ABTS and DPPH.